النص القرآني في منظور الدراسة الأدبية: الموقف والمنهج (Quranic text from the perspective of Literary Study: View and Methodology) - (Abdel Rahman Bin Rajallah al-Jamiey al-Salmiy), عبدالرحمن بن رجا الله (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: يناقش البحث مسألة مهمة وهي: النص القرآني في منظور الدراسة الأدبية. وقد تناول الباحث بداية ظهور هذه الدعوة على يد الأستاذ أمين الخولي وبين أهم القضايا التي آلت إليها دعوة الخولي. والتي من أبرزها: نزع قداسة النص القرآني، والتأكيد على عروبة النص القرآني وإغفال عالميته، واختزال فهم النص القرآني في التفسير الأدبي وإسقاط المصطلحات النقدية على النص القرآني. كما تناول البحث موقف الفكر العلماني الحديث من هذه الدعوة وكيف انطلق منها في قرآته التأويلية للنص القرآني بهدف نزع قداسته وتفريغه من محتواه الديني. ثم تناول الباحث القراءة الإسقاطية للنص القرآني عند منظري إسلامية الأدب وأبرز الإشكاليات التي وقع فيها بعض الباحثين عندما تعاملوا مع النص القرآني باعتباره نصاً أدبياً صرفاً وإرثاً فنياً بحتاً. الكلمات المفتاحية: الجذور- النشأة- الخولي- عروبة النص- الاختزال. Abstract: The paper attempt to dwell on a significant issue: the position of the Qur’anic text from the perspective of literary study. The questions raised by al-Khouly in this regard were evoked: shall the holy text be stripped of its sacredness? Shall its Arabic be authenticated? Shall the universality of its message be disregarded? Shall the interpretation from the verses adorned with literary features be abandoned? Will it be proper to use literary terms for the styles of the Quran? This paper also deals with the modern secular view that propagate this call and how the resulted interpretation is in actuality an attempt to deny the sacredness and religiousness that the contents have. A sample of this type of reading of the Quran will be studied and analysed. Some of the errors committed by those critics who follow the method of treating Qur’anic texts as literary texts will be subjected to discussion. Keywords: Roots – Development – al-Khouly- Textual Arabic – Omitting. Abstrak: Kajian ini membincangkan tentang satu isu penting iaitu Al-Quran dari sudut kajian sastera. Penyelidik membicarakan sejarah permulaan kepada seruan ni yang diasaskan oleh Amin Al-khuli kemudian membahaskan beberapa isu-isu penting yang dibangkitkan oleh beliau seperti perdebatan tentang kesucian Al-Quran, penekanan terhadap identiti Al-Quran yang dikatakan ia turun hanya untuk bangsa Arab dan menafikan sifatnya yang universal, serta meringkaskan pemahaman terhadap teks Al-Quran dalam huraian sastera dengan meninggalkan istilah wacana kritis dalam teks Al-Quran. Dalam masa yang sama, penyelidik turut menyentuh tentang pemikiran sekular moden dalam seruan ini dan bagaimana untuk mematahkan pemikiran ini yang sering mentakwilkan ayat-ayat Al-Quran dengan tujuan meragukan keasliannya dan memisahkan isi kandungan agama yang dibawa oleh Al-Quran. Justeru, penyelidik akan membahaskan teks Al-Quran dari perspektif sastera islam dan membincangkan beberapa permasalahan yang telah dibangkitkan oleh beberapa pengkaji yang mengkaji dan menganggap teks Al-Quran sebagai teks sastera dan seni semata-semata. Kata kunci: Asal Usul - Kelahiran – Al-Khuli – Identiti Teks – Ringkasan.